The misleading of public participation in environmental assessment – exploring four infrastructure cases in Denmark. Issue 3 (4th May 2018) - Elling, Bo; Nielsen, Helle Nedergaard
ABSTRACT: The article analyses the recent development of public participation in environmental assessment and indicates some unfortunate and unintended results. A number of Danish cases show how the tools involved are employed for a kind of 'acceptance planning', instead of actual environmental protection, and that the legitimacy which public inclusion was supposed to bring to environmental assessment has instead been replaced by considerations of legality, which frees entrepreneurs and authorities from including real environmental considerations in their planning. Thus, the undesirable handling of public participation that the article analyses is not only due to the actual difficulties of practising inclusion and the indisputable complexity of the environmental issues but also to a very large extent due to considerations of economic efficiency and an unwillingness among investors – public as well as private – to take account of environmental consequences as a long-term issue. The article ends with a range of recommendations for securing public inclusion in matters of environmental assessment through independent public initiatives or institutions that do not answer to authorities and entrepreneurs.